(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article explores the views, the global importance of the spiritual heritage of the great muhaddis, amirul-muminin Imam al - Bukhari in the science of Hadith, in student-youth education, as well as the moral educational significance of scholar’s works in the development of enlightenment qualities in youth education and the formation of positive qualities.